APPLICATION OF THE OPEN METHOD (MD3E) IN THE ERGONOMIC DESIGN OF PRODUCTS (Human Factors in Design, 2012)
According to Ferreira et al (2003), the activity of developing products takes on a prominent posture in the corporate world, constituting an important factor of competition. In order to carry out a product design a method should be applied to promote safety and increase the chances of success. In this article, two standards of methodologies will be discussed: open and closed. Initially, closed methods focused on Ergonomics will be presented. Later on, there is a differentiation on the open and closed methods, through the exposure of the open Method of Deployment in 3 Stages (MD3E) and its application in the field of Ergonomics. On dealing with an open method, the user can intervene in its stages to adapt them to their work, once it is not configured as a ready-made model. Bibliographical and field researches were used to achieve the end results of this research project.